2010
DOI: 10.31390/cosa.4.2.03
|View full text |Cite
|
Sign up to set email alerts
|

On the non-classical infinite divisibility of power semicircle distributions

Abstract: Abstract. The family of power semicircle distributions defined as normalized real powers of the semicircle density is considered. The marginals of uniform distributions on spheres in high-dimensional Euclidean spaces are included in this family and a boundary case is the classical Gaussian distribution. A review of some results including a genesis and the so-called Poincaré's theorem is presented. The moments of these distributions are related to the super Catalan numbers and their Cauchy transforms in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
(53 reference statements)
2
17
0
Order By: Relevance
“…Therefore, φ(µ) ≤ γ 1 /γ 0 from Theorem 3.3. The last proposition extends Theorem 3.7 in [5] which gives an upper bound for the divisibility indicator in terms of the Boolean kurtosis: Kurt ⊎ (µ) ≥ φ(µ). Indeed, for a probability measure with mean zero and finite fourth moment, we have Kurt ⊎ (µ) = (γ 1 + β 2 1 )/γ 0 ≥ γ 1 /γ 0 .…”
Section: On Jacobi Parameters and Free Meixner Lawssupporting
confidence: 66%
“…Therefore, φ(µ) ≤ γ 1 /γ 0 from Theorem 3.3. The last proposition extends Theorem 3.7 in [5] which gives an upper bound for the divisibility indicator in terms of the Boolean kurtosis: Kurt ⊎ (µ) ≥ φ(µ). Indeed, for a probability measure with mean zero and finite fourth moment, we have Kurt ⊎ (µ) = (γ 1 + β 2 1 )/γ 0 ≥ γ 1 /γ 0 .…”
Section: On Jacobi Parameters and Free Meixner Lawssupporting
confidence: 66%
“…(a) The first identity in Proposition 2 is actually the consequence of an integral transformation due to Zolotarev -see (2.2.19) with β = 1 in [58]. We have offered a separate proof which is perhaps clearer, and which enhances the similarities between the free and the classical case echoing those between (3) and (4). Observe in particular the identity…”
Section: 3mentioning
confidence: 85%
“…The law β a = β 1−a,1+a is FID if (and only if) 1 2 ≤ |a| < 1 [AH13a]. The free infinite divisibility for ultraspherical distributions u p was conjectured for p ≥ 1 in [AP10,Remark 4.4], and Arizmendi and Belinschi [AB13] showed that the ultraspherical distribution u n (and also the beta distribution β 1 2 ,n+ 1 2 ) is FID for n = 1, 2, 3, · · · . For beta prime distributions, β ′ 2/3,1/2 is a free stable law and so is FID [BP99, p. 1054].…”
Section: Resultsmentioning
confidence: 99%